Protein Profiling of Several Malaysian Freshwater Fish by Two-Dimensional Electrophoresis - Masdor, Nor Azlina (2004)
A proteornics approach using 2D-PAGE was initiated to investigate protein expression in fish organs especially hepatopancreas, with the aim of providing fish protein expression maps that are seriously lacking in the literature. Two dimensional electrophoresis maps of hepatopancreas from Jelawat (Leptobarbus hoevenii), Catfish (Clarias batrachus), Red tilapia (Oreochromis mossambicus), Patin (Pangasius pangasius) and Lampam Jawa (Puntius gonionotus); all Malaysian freshwater fish species were constructed. The soluble protein sample was analyzed by two dimensional electrophoresis, using immobilized pH gradient strip (pH 3-10) and 15% gel acrylamide. 200 protein spots from Red Tilapia and 44 spots from Catfish were observed. Compari sons of similarities in terms of protein spots in the fish species were made using ruler measurements and superimposing the electropherogram of one fish species with the other to confirm spots coordinate similarities. The maximum matching found in terms of pI and molecular weight coordinate is limited to a maximum of three fish species. Patin-Lampam Jawa-Jelawat and Lampam Jawa-Red tilapia-Jelawat share the most number of spots at 8 spots. At the two-fish comparison level, the highest number of same spots was found in Red tilapia-Jelawat (33 spots) followed by Lampam Jawa-Jelawat (25 spots), Lampam Jawa-Red tilapia (20 spots), Patin-Lampam Jawa (17 spots), Patin-Red tilapia, Patin- Jelawat and Lampam Jawa-Catfish; all with 12 same spots.